Pengaruh Kepemimpinan Kepala Sekolah dan Motivasi Kerja terhadap Kinerja Guru - Damayani, Titin; Arafat, Yasir; Eddy, Syaiful (Yayasan Sembilan Pemuda Indonesia, 2020)
This study aimed at determining whether there is 1) an influence of the principal's leadership on the performance of the teachers; 2) an influence of work motivation on the performance of teachers; 3) an influence of the principal's leadership and work motivation together on the performance of the teachers. This study used a quantitative method. The research sample consisted of 103 junior high school teachers in Sungai Lilin. The data were collected using questionnaire. Data analysis techniques used 1) descriptive quantitative analysis techniques; and 2) multiple regression. The results of the study state that 1) there was a significant influence between the leadership of the principal on the performance of the teachers; 2) there was a significant influence between work motivation on the performance of teachers; 3) there was a significant influence jointly between the leadership of the principal and work motivation on the performance of the teachers.